2002
DOI: 10.1073/pnas.102055799
|View full text |Cite
|
Sign up to set email alerts
|

Reduced immunopathology and mortality despite tissue persistence in aMycobacterium tuberculosismutant lacking alternative σ factor, SigH

Abstract: The pathogenesis of tuberculosis involves multiple phases and is believed to involve both a carefully deployed series of adaptive bacterial virulence factors and inappropriate host immune responses that lead to tissue damage. A defined Mycobacterium tuberculosis mutant strain lacking the sigH-encoded transcription factor showed a distinctive infection phenotype. In resistant C57BL͞6 mice, the mutant achieved high bacterial counts in lung and spleen that persisted in tissues in a pattern identical to those of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
228
1
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(242 citation statements)
references
References 43 publications
(32 reference statements)
8
228
1
4
Order By: Relevance
“…The mycobacterial growth rate in guinea pigs is not the only indicator of virulence, and studies have shown that strains with no differences in in vivo growth rates can produce infections that differ significantly by histopathological analysis 46,47 . Despite the reduced bacterial loads, histopathological assessments revealed that lung sections from guinea pigs infected with DmazF3D9D6 exhibited higher degrees of granulomatous inflammation than guinea pigs infected with the parental strain (Fig.…”
Section: Mazf Ribonucleases Are Required For Persistence In Vitromentioning
confidence: 99%
“…The mycobacterial growth rate in guinea pigs is not the only indicator of virulence, and studies have shown that strains with no differences in in vivo growth rates can produce infections that differ significantly by histopathological analysis 46,47 . Despite the reduced bacterial loads, histopathological assessments revealed that lung sections from guinea pigs infected with DmazF3D9D6 exhibited higher degrees of granulomatous inflammation than guinea pigs infected with the parental strain (Fig.…”
Section: Mazf Ribonucleases Are Required For Persistence In Vitromentioning
confidence: 99%
“…Reduced pathology in the absence of any detectable change in bacterial load has previously been reported for M. tuberculosis mutants lacking the sigH (Kaushal et al, 2002) and whiB3 (Steyn et al, 2002) genes, and differences in the rate of progression of pathology have been observed between clinical isolates of M. tuberculosis that differ in their ability to elicit a proinflammatory immune response (Manca et al, 2001). One possible explanation for the reduced pathology phenotype of the Dacr2 mutant is that the Acr2 protein itself elicits some detrimental form of immune response that promotes tissue destruction without affecting the bacterial population.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the Ϫ10 and Ϫ35 boxes identified to date vary largely, and the Ϫ35 region in particular tolerates a high level of sequence diversity (75). Recently, the consensus sequences for SigH (17,18) and SigE (16) have been described. However, Rv1394c and Rv1395 promoters do not fit with these elements, suggesting that they are probably recognized by other sigma factors.…”
Section: Discussionmentioning
confidence: 99%